Course outline: Research Methodology for Sustainability Science - Zen, Irina Safitri (2021)
A new course proposed at the post-graduate level on Sustainability Science is a compulsory course for the student to begin the thesis and or research project. The course outline of Research Method for Sustainability Science to promote inter-and transdisciplinary approaches. The three-unit course will well-equipped students with the basic competency of sustainability science; systemic thinking, strategic thinking, future thinking, normative and anticipatory while fulfilling standard Malaysia Quality Assurance through Bloom's taxonomy.